2009
DOI: 10.1148/radiol.2512080553
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pathologic Response to Neoadjuvant Chemotherapy in Breast Cancer by Using MR Imaging and Quantitative1H MR Spectroscopy

Abstract: Patients who show greater reduction in tCho compared with changes in tumor size are more likely to achieve pCR. The change in tumor size halfway through therapy was the most accurate predictor of pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
123
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 35 publications
6
123
1
1
Order By: Relevance
“…Thus, some of the responders from RECIST were redefined as nonresponders, leading to significant changes in the DCE-MRI-derived parameters for both responders and nonresponders using the modified RECIST. A broad variety of response criteria exists in the literature, concerning both the degree of tumor reduction that defines a responder and the method used to measure the tumor size (8,9,11,14,16,36,37). Therefore, it is important to notice that the different response criteria will have an impact on the interpretation of DCE-MRI-derived parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, some of the responders from RECIST were redefined as nonresponders, leading to significant changes in the DCE-MRI-derived parameters for both responders and nonresponders using the modified RECIST. A broad variety of response criteria exists in the literature, concerning both the degree of tumor reduction that defines a responder and the method used to measure the tumor size (8,9,11,14,16,36,37). Therefore, it is important to notice that the different response criteria will have an impact on the interpretation of DCE-MRI-derived parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been reported for diagnosis (7), therapy response monitoring (8,9), and survival prediction (10)(11)(12). Both semiquantitative (calculated directly from the contrast uptake curves) and pharmacokinetic parameters (based on kinetic modeling of the contrast uptake curves) (13) can be obtained by analyzing MRI data from the breast.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a simple dichotomous approach based on the presence or absence of the choline peak was shown in some reports (5,6). Furthermore, choline quantification has been proposed using either an internal or an external reference (9,10). Recently, Sardanelli et al (7) showed that breast MRS using the integral value of the choline peak allowed a high level of diagnostic performance, with 84% sensitivity and 89% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MRS has been also applied in other organs such as the prostate and breast (4)(5)(6). Regarding the breast, MRS has been shown to be useful for the differentiation between benign and malignant lesions and for the monitoring of early response to neoadjuvant chemotherapy (7)(8)(9). Its diagnostic value for breast cancer is typically based on the detection of elevated levels of choline compounds, which are markers of active tumors (10,11).…”
mentioning
confidence: 99%